Endothelial function in patients with chronic obstructive pulmonary disease: a systematic review of studies using flow mediated dilatation. (2nd December 2017) - Vaes, Anouk W.; Spruit, Martijn A.; Theunis, Jan; Goswami, Nandu; Vanfleteren, Lowie E.; Franssen, Frits M.E.; Wouters, Emiel F.M.; De Boever, Patrick
ABSTRACT: Background : Cardiovascular disease is an important cause of morbidity and mortality in chronic obstructive pulmonary disease (COPD). Endothelial function may be involved in the pathogenesis of cardiovascular disease. In contrast to the attention given to pulmonary endothelial dysfunction, little is known about peripheral vascular changes in COPD. Therefore, we reviewed the literature on peripheral endothelial function in COPD. Methods : Databases were screened for studies using ultrasound-based flow-mediated dilation (FMD), the reference method for assessing peripheral endothelial function, in stable COPD patients. Pooled effect sizes were calculated using random effects model. Results : 17 studies were identified, with a total of 1228 participants (724 COPD patients; 504 controls). Pooled analysis demonstrated an impaired endothelial-dependent FMD (−3.22%; 95% confidence interval (CI) −4.74 to −1.69; p < 0.001; I 2  = 96%) and endothelial-independent FMD (−2.86%; 95%CI −5.63 to −0.09; p = 0.04; I 2  = 83%) in COPD patients when compared with smoking and non-smoking controls. Conclusion : This review provides evidence for impaired peripheral endothelial function in COPD. Since impaired endothelial function may contribute to cardiovascular morbidity, a more comprehensive cardiovascular phenotyping is considered important in COPD to address cardiovascular risk. A high frequency of cardiovascular comorbidity is observed in COPD patients, and therefore well-controlled, larger studies that investigate endothelial function in COPD patients are recommended.